Female pelvic shape: Distinct types or nebulous cloud? - Kuliukas, A.; Kuliukas, Lesley; Franklin, D.; Flavel, A. (MA Healthcare Ltd, 2015)
The objective of this study was to re-evaluate the Caldwell-Moloy (1933) classification of female pelvic shape, which has been traditionally, and still is currently, taught to students of midwifery and medicine. Using modern pelvimetric methodologies and geometric morphometric (GM) analysis techniques, we aim to elucidate whether these classic female pelvic types are an accurate reflection of the real morphometric variation present in the female human pelvis. GM analysis was carried out on sets of pelvic landmarks from scans of women living in a contemporary Western Australian population. Sixty-four anonymous female multi-detector computer tomography (MDCT) scans were used for most of the study and 51 male scans were also examined for comparison. Principle component analysis (PCA) found that there was no obvious clustering into the four distinct types of pelvis (gynaecoid, anthropoid, android and platypelloid) in the Caldwell-Moloy classification, but rather an amorphous, cloudy continuum of shape variation. Until more data is collected to confirm or deny the statistical significance of this shape variation, it is recommended that teachers and authors of midwifery, obstetrics and gynaecological texts be more cautious about continuing to promote the Caldwell-Moloy classification, as our results show no support for the long taught ‘four types’ of pelvis.